Effects of Heat Treatment on Morphology, Texture, and Mechanical Properties of a MnSiAl Multiphase Steel with TRIP Behavior - Salinas, Alvaro; Artigas, Alfredo; Perez Ipiña, Juan; Castro Cerda, Felipe; Garza Montes de Oca, Nelson Federico; Colás Ortíz, Rafael; Petrov, Roumen; Monsalve G., Alberto (Molecular Diversity Preservation International, 2018)
The effect that the microstructure exerts on the TRIP phenomenon and on the mechanical properties in a multiphase steel was studied. Samples of an initially cold-rolled ferrite-pearlite steel underwent different intercritical annealing treatments at 750 °C until an equal fractions of austenite/ferrite was reached; the intercritical treatment was followed by isothermal bainitic treatments before cooling the samples to room temperature. Samples in the first treatment were heated directly to the intercritical temperature, whereas other samples were heated to either 900 or 1100 °C to obtain a fully homogenized, single phase austenitic microstructure prior to the conducting the intercritical treatment. The high temperature homogenization of austenite resulted in the decrease in its stability, so a considerable austenite fraction transformed into martensite by cooling to room temperature after the bainitic heat treatment. Most of the retained austenite transformed during the tensile tests, and as a consequence, the previously homogenized steels showed the highest UTS. In turn, the steel with a ferritic-pearlitic initial microstructure, exhibited higher ductility than the other steels and texture components that favor forming processes.